Level of Foxp3, DNMTs, methylation of Foxp3 promoter region, and CD4 + CD25 + CD127low regulatory T cells in vulvar lichen sclerosus - Lin Wang; Jin‐Ling Yi; Hai‐Yan Chen; Pei‐Liang Wang; Yan‐Li Shen (Kaohsiung Journal of Medical Sciences, 2021)
Abstract This study is to investigate the pathogenesis of vulvar lichen sclerosus (VLS) by analyzing the level of Foxp3, DNMTs, methylation of Foxp3 promoter region, and CD4 + CD25 + CD127low Regulatory T cells (Tregs). This study enrolled 15 VLS patients and 25 controls. Lesional and extralesional vulvar skin tissues, normal vulvar skin tissues and peripheral blood were collected. Compared with the control group, Foxp3 protein in the lesional and extralesional skin of VLS group was significantly reduced. The levels of DNMT1 and DNMT3b proteins in lesional skin of VLS group were significantly increased. There was no difference in the total methylation rates of the promoter region of the Foxp3 gene. The methylation rates of CpG1, CpG4, CpG9, and CpG10 were significantly higher in lesional skin of VLS group than in control group. There was no correlation between the total methylation rates of 10 CpG sites and the level of Foxp3 and DNMT1 proteins; there was a positive correlation between Foxp3 and DNMT1 protein in lesional skin of VLS group (r = 0.675, p < 0.05), and a negative correlation (r = −0.665, p < 0.05) in extralesional skin of VLS group. However, there was no correlation of Foxp3 with DNMT3b. The number of CD4 + CD25 + CD127low Tregs VLS decreased significantly. The expression of Foxp3 protein and the quantity of CD4 + CD25 + CD127low Tregs in patients with VLS decreased, which may cause local or systemic abnormal immunosuppression of Tregs, leading to the occurrence of VLS. This may be related with methylation or DNMT1, which needs further verification.